Effects of aquatic exercise on appetitive responses in adolescents with obesity: An exploratory study. (1st June 2023) - Miguet, M.; Pereira, B.; Beaulieu, K.; Finlayson, G.; Matłosz, P.; Cardenoux, C.; Boirie, Y.; Duclos, M.; Thivel, D.; Metz, L.
Abstract: Aquatic exercise has been suggested as a beneficial modality to improve weight loss, cardiorespiratory fitness and quality of life in adolescents with obesity; however, its impact on appetite control in youth remains unknown. The aim of this preliminary study was to examine the effect of an acute aquatic exercise session on energy intake (EI), appetite feelings and food reward in adolescents with obesity. Twelve adolescents with obesity (12–16 years, Tanner stage 3–5, 9 males) randomly completed two conditions: i) control (CON); ii) aquatic exercise session (AQUA). One hour before lunch, the adolescents stayed at rest outside the water in a quiet room for 45 min on CON while they performed a 45-min aquatic exercise session on AQUA. Ad libitum EI and macronutrients were assessed at lunch and dinner, subjective appetite feelings taken at regular intervals, and food reward measured before and after lunch. Paired T-test showed that EI was not different between CON and AQUA at lunch (1333 ± 484 kcal vs 1409 ± 593 kcal; p = 0.162) and dinner (528 ± 218 kcal vs 513 ± 204 kcal; p = 0.206). Total daily ad libitum EI was significantly higher on AQUA (1922 ± 649 kcal) compared with CON (1861 ± 685 kcal; p = 0.044) but accounting for the exercise-induced energy expenditure, relative energy intake did not differ (2263 ± 732 kcal vs 2117 ± 744 kcal, p = 0.304). None of the appetite feelings (hunger, fullness, prospective food consumption and desire to eat) and food reward dimensions were significantly different between conditions. These preliminary and exploratory results suggest that an acute aquatic-exercise session might not induce energy compensatory responses in adolescents with obesity.